Early Evidence of Cardiotoxicity and Tumor Response in Patients with Sarcomas after High Cumulative Dose Doxorubicin Given as a Continuous Infusion. (26th September 2017) - Quintana, Raymundo A.; Banchs, Jose; Gupta, Ridhi; Lin, Heather Y.; Raj, Sean D.; Conley, Anthony; Ravi, Vinod; Araujo, Dejka; Benjamin, Robert S.; Patel, Shreyaskumar; Vadhan-Raj, Saroj; Somaiah, Neeta
Abstract : Background . Despite the dose-dependent response rate of sarcomas to doxorubicin, clinicians limit its cumulative dose due to cardiotoxicity. This study evaluates early evidence of cardiotoxicity in patients treated with high-dose doxorubicin given as a continuous infusion. Methods . Data was collected on patients who received 90 mg/m 2 doxorubicin as a continuous infusion and 10 gm/m 2 ifosfamide for up to 6 cycles as part of a phase II study. Cardiotoxicity was assessed with serial echocardiograms or multigated acquisition scans and serum brain natriuretic peptide and troponin levels. Tumor responses were determined by serial radiographic imaging per RECIST. Result . Out of the 48 patients enrolled, no patient developed heart failure symptoms; however, 4 out of the 38 (10%) patients with serial left ventricular ejection fraction assessments developed subclinical cardiotoxicity (asymptomatic drop in LVEF ≥ 10%). Twenty-three patients received all six 72-hour cycles of doxorubicin with a mean cumulative dose of 540 mg/m 2 . Among these patients, 4% (n = 1 ) developed subclinical cardiotoxicity. In the advanced disease group (n = 39 ), patients with a complete or partial response received a higher mean cumulative dose than those with stable disease (p < 0.033 ). Conclusions . Doxorubicin cardiotoxicity can be limited by administering doxorubicin as a continuous infusion, allowing higher cumulative dosing to maximize efficacy.